Petrographic characteristics and mechanical properties of rocks from Khagram-Razagram area, Lower Dir, NWFP, Pakistan - Sajid, Muhammad; Arif, Mohammad; Muhammad, Noor (Journal of Himalayan Earth Sciences, 2009)
The Khagram-Razagram area, consists of rocks of the Kamila amphibolite belt, which constitutes the southern portion of the intra-oceanic Kohistan island arc. Field observations and detailed petrographic studies of representative samples reveal that the area largely consists of two major rock types, namely epidote amphibolite and gabbro-norite. The epidote amphibolites are sub-equigranular, fine to coarsegrained, xenoblastic, and foliated along shear zones. They consist of abundant hornblende, plagioclase, epidote, quartz and accessory amounts of sphene, apatite and ore minerals. The gabbro-norites are subequigranular, medium- to coarse-grained, hypidiomorphic to idiomorphic and massive, i.e. without any preferred orientation of grains. They essentially consist of plagioclase, orthopyroxene and clinopyroxene with accessory amounts of epidote and quartz. Some of the engineering properties of the petrographically investigated epidote amphibolite and gabbro-norite were also determined in the course of this study. These include unconfined compressive strength, unconfined tensile strength, shear strength, specific gravity and water absorption. The values of specific gravity and water absorption of both the epidote amphibolite and gabbro-norite are within the range permissible for their use as dimension stones and construction material. Comparison of the petrographic characteristics of the two rock types with their respective strengths reveals that modal mineralogy, grain size and shapes, degree of alteration and foliation have a significant effect on the strength of these rocks.